A case of ulcerative colitis presenting as pyoderma gangrenosum and lung nodule - Xin Li; Subhash Chandra (Greater Baltimore Medical Center, 2014)
Pyoderma gangrenosum is a phenomenon of cutaneous ulceration where etiology is not well understood. About half of the cases have an associated extracutanoeus manifestation or associated systemic diseases. Most commonly associated systemic disorders include inflammatory bowel disease, hematologic malignancies, autoimmune arthritis, and vasculitis. We are reporting a case where pyoderma gangrenosum has presenting features for ulcerative colitis.